Reflectance spectroscopy and analytical techniques in characterising PGE-bearing host rocks - K. Tamilarasan; S. Anbazhagan; S. Ranjithkumar (Geosystems and Geoenvironment, 2023)
The Mettuppalaiyam mafic and ultramafic complex (MUC) is part of the Southern Granulite terrain in India. MUC is one of the promising sites for Ni-Cu-Cr and Platinum Group of Elements (PGE) mineralisation. The Geological Survey of India (GSI) has conducted geological and geochemical studies at the Mettuppalaiyam complex in different periods to assess PGE concentration in the mafic and ultramafic rocks. Mafic-ultramafic rock samples from the Solavanur, Mallanayakkanpalaiyam and Karappadi blocks of the Mettuppalaiyam complex were used in the present study to acquire reflectance spectroscopic measurements. Twenty-three rock samples with mafic, ultramafic and intermediate compositions were collected. The reflectance spectra were obtained under 350 nm-2500 nm spectral range using ASD FieldSpec Pro® spectroradiometer. The continuum-removed reflectance spectra provide diagnostic absorption features for various host rocks. The influence of elemental composition and associated key minerals in the rock samples on absorption bands was critically analysed.The XRF method was adopted to analyse the chemistry of host rocks. The XRD analysis was carried out from selected rock samples to assess the dominant and key minerals in the host rocks. The XRD and XRF analysis results correlated with the absorption features. The absorption features in the UV–visible spectrum are mainly due to the electronic process of transition metal ions and charge transfer of metals. The overtones and vibration spectra of Al-OH, Fe-OH, Mg-OH and carbonate ions in the rock samples influence the absorption bands in the SWIR region. The absorption bands are due to key minerals like clinochlore/chlorite, actinolite, antigorite and amphiboles. The ore microscopic study, HR-ICPMS and SEM EDAX analyses show encouraging results of PGE concentration in host rocks and validated the spectral results.